1999
DOI: 10.1002/(sici)1521-186x(199909)20:6<347::aid-bem3>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Induction of stress proteins by electromagnetic fields in cultured HL-60 cells

Abstract: HL‐60 cells in culture were exposed for 2 h to a sinusoidal 0.1 or 1 mT (1 or 10 Gauss) magnetic field at 60 Hz and pulse labeled after exposure with radioactive isotopes by incubation by using either [35S]methionine, [3H]leucine, or [33P]phosphate. The radioactive labels were incorporated into cellular proteins through synthesis or phosphorylation. Proteins were extracted from electrostatically sorted nuclei, and the heat shock/stress proteins (sp) were analyzed for synthesis and phosphorylation by two‐dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 66 publications
2
35
1
1
Order By: Relevance
“…In human breast cells, they found that a 1-hr EMF exposure or a repeated 20-min EMF exposure led to 30-40% increases in HSP70 protein (30). More recently, Pipkin et al (44) reported that both HSP70 and HSP27 were induced in HL-60 cells after a 1 mT EMF exposure for 2 hr.…”
Section: Discussionmentioning
confidence: 99%
“…In human breast cells, they found that a 1-hr EMF exposure or a repeated 20-min EMF exposure led to 30-40% increases in HSP70 protein (30). More recently, Pipkin et al (44) reported that both HSP70 and HSP27 were induced in HL-60 cells after a 1 mT EMF exposure for 2 hr.…”
Section: Discussionmentioning
confidence: 99%
“…Miyakawa et al [2001] found that the temperature required for a given expression of a reporter gene (lacZ) under HSP16 promoter control in transgenic nematode worms was reduced after exposure to a 60 Hz magnetic field at up to 0.5 T. Leszczynski et al [2002] saw an increase in protein phosphorylation and Hsp27 expression after exposure to a 900 MHz GSM signal. Other reports, discussed previously, have found magnetic field influences on Hsp16 activity in nematodes [Junkersdorf et al, 2000], as well as Hsp27 in cell cultures [Pipkin et al, 1999;Tokalov and Gutzeit, 2004]. Controversy exists for studies of HSP27 as well, and no effect was seen in several papers [Guisasola et al, 2002;Shi et al, 2003;Coulton et al, 2004;Lim et al, 2005].…”
Section: Mechanisms: Heat Shock Proteinsmentioning
confidence: 93%
“…The magnetic field exposure was also able to enhance the HSP response following 43 8C heat stress. Pipkin et al [1999] found no response from a 2-h 60 Hz exposure at 100 mT, but did see an increase in Hsp70, as well as some other heat shock proteins (Hsp27, Hsp90) at 1 mT. At that field strength, the authors found their coils were heating the incubator and employed a water cooling system to counter that problem.…”
Section: Mechanisms: Heat Shock Proteinsmentioning
confidence: 98%
“…Hsps proteins play a critical role in the regulation of the cell cycle, proliferation and apoptosis. The synthesis of Hsp can be produced under several stress conditions: alcohol, oxidative stress, osmotic pressure change, toxic chemicals and exposure to low-frequency EMF (Pipkin et al, 1999;Leszczynski et al, 2002). Our future research will be devoted to study the quantification of Hsp-70, Bcl-2 and Cx43 proteins, in control and irradiated samples, possible increased [Ca 2+ ] i concentration process and the implication of the anti-apoptotic increase of Bcl-2 protein promoting cell survival (Takuma et al, 2004). 3.…”
Section: Resultsmentioning
confidence: 99%